The moderating role of organizational commitment on the relationship between training and teacher's performance of public secondary schools - Abdullahi, Abubakar Sadiq (2017)
In all education system, the performance of teachers is one of the fundamental factors determining school effectiveness and learning outcomes.It is becoming worrisome to note that the performance of these teachers specifically in Bauchi state has taken a negative shape. Hence, this study examined the effect of training on teachers’ performance and the role of organizational effective commitment. A survey research design was used and data were collected from 354 public secondary school teachers in Bauchi Metropolis by using using Newman et’al perceived training availability scale, Allen & Meyer’s organizational affective commitment scale and Koopman’s task performance scale.The study utilized hierarchical multiple regression analysis and the results indicated a significant positive effect of training on teachers performance. The results further revealed that organizational affective commitment has potential moderating effect on the relationship between training and teachers’ performance among public secondary schools in Bauchi Metropolis.The study base the findings, therefore recommended for institution of training program on a regular basis. Also effort should be made to stimulate teachers’ commitment to the various schools they work.